The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1242/jeb.104505
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phenotypic flexibility enhances energy savings during winter fast in king penguin chicks

Abstract: Energy conservation is a key priority for organisms that live in environments with seasonal shortages in resource supplies or that spontaneously fast during their annual cycle. The aim of this study was to determine whether the high fasting endurance of winteracclimatized king penguin chicks (Aptenodytes patagonicus) is associated with an adjustment of mitochondrial bioenergetics in pectoralis muscle, the largest skeletal muscle in penguins. The rates of mitochondrial oxygen consumption, and ATP synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 41 publications
5
74
2
Order By: Relevance
“…Leak respiration in the liver was significantly greater in high-SMR individuals, while MMR was positively related to leak respiration in the muscle. These results are consistent with other studies comparing experimental groups or taxa that have shown animals with higher metabolism to have higher leak respiration (Rolfe and Brand 1997;Brookes et al 1998;Jacobs et al 2012;Salin et al 2012;Monternier et al 2014; but see Larsen et al 2011). Though there is a need for some mitochondrial ATP to support diverse cellular activities in vivo, the low respiration rate under basal conditions (i.e., SMR or BMR) results from both basal ATP demand and the effects of mitochondrial proton leak (Kadenbach 2003;Brand and Nicholls 2011).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Leak respiration in the liver was significantly greater in high-SMR individuals, while MMR was positively related to leak respiration in the muscle. These results are consistent with other studies comparing experimental groups or taxa that have shown animals with higher metabolism to have higher leak respiration (Rolfe and Brand 1997;Brookes et al 1998;Jacobs et al 2012;Salin et al 2012;Monternier et al 2014; but see Larsen et al 2011). Though there is a need for some mitochondrial ATP to support diverse cellular activities in vivo, the low respiration rate under basal conditions (i.e., SMR or BMR) results from both basal ATP demand and the effects of mitochondrial proton leak (Kadenbach 2003;Brand and Nicholls 2011).…”
Section: Discussionsupporting
confidence: 89%
“…This is because MMR was measured during peak excess postexercise oxygen consumption (EPOC), when the major requirement for oxygen is in the removal of lactate and the restoration of cellular homeostasis, which is supported by white muscle (Wood 1991). However, given that white muscle contributes approximately 35% to the total body mass of a trout (calculated according to Houlihan et al 1986), it is perhaps surprising that white muscle mitochondria did not explain any of the substantial variation in SMR, in contrast to that relationship reported in other species (Rolfe and Brand 1996;Monternier et al 2014). Instead, only the bioenergetics of the liver contributed to the variability in SMR.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although such metabolic changes provide immediate lifesaving responses, medium-to long-term costs associated with metabolic changes during fasting remain little investigated in wild species that typically cope with repeated and sometimes prolonged periods of food shortage (Vázquez-Medina et al, 2010). Because mitochondria are cornerstone organelles implicated in metabolic responses to fasting (Monternier et al, 2014), but also the first site of production of damaging reactive oxygen species (ROS) (Andreyev et al, 2005), direct oxidative costs to prolonged fasting may be expected (e.g. Chausse et al, 2015;Geiger et al, 2012;Sorensen et al, 2006;Wasselin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although winter-acclimatized king penguin chicks retain a high capacity for thermogenesis (Duchamp et al, 1989), such starvation resistance reflects their ability to store energy as fat (34% adiposity in the pre-winter period) and control its allocation to minimize energy expenditure (growth arrest, lower basal metabolic rate, shallow hypothermia, reduced thermogenic effect of lipids) in order to maximize energy conservation (Duchamp et al, 1989;Cherel et al, 1993Cherel et al, , 2004Eichhorn et al, 2011;Teulier et al, 2013). In a recently published paper, it was shown that skeletal muscle mitochondria from fasted winteracclimatized chicks minimized the cost of ATP synthesis by increasing the efficiency of oxidative phosphorylation processes, which would ultimately alleviate the need for energy substrates (Monternier et al, 2014). This finding is of particular interest for at least two reasons.…”
Section: Introductionmentioning
confidence: 99%